Black oxide coating and its effectiveness on prevention of hydrogen uptake. Issue 1 (2nd January 2019) - Ooi, S. W.; Yan, P.; Vegter, R. H.
ABSTRACT: A simple thermal immersion test with constant heating rate is shown to be an effective method for investigating hydrogen uptake from the decomposing lubricant. It is proven that the black oxide coating can be used as a barrier to hydrogen uptake. Detailed microstructure and composition characterisation of the black oxide layer were also performed.